2020
DOI: 10.1101/2020.06.29.20142554
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Citywide Nucleic Acid Screening of SARS-CoV-2 Infections in Post-lockdown Wuhan, China: Results and Implications

Abstract: Background: After the outbreak of Coronavirus disease in 2019 (COVID-19), stringent lockdown measures were imposed in Wuhan between January 23, 2020 and April 8, 2020. To provide evidence on the post-lockdown risk of COVID-19 epidemic in Wuhan, the city government conducted a citywide nucleic acid screening of SARS-CoV-2 infection between May 14 and June 1, 2020. Methods: All city residents aged ≥6 years were potentially eligible to participate the screening programme. The rate of detection of asymptomatic inf… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The authors of 15 (46.9%) of the 32 studies that used serological tests reported their own validation test performance, while in 13 (40.6%), the validation performed by other studies or by the manufacturer was described. Excluding Wuhan's (China) screening programme 17 that tested 9,899,828, at least 394,090 individuals were tested in the other 36 studies that reported the number of tests. However, this number was highly variable among studies (mean: 10,946.94, median: 1990, standard deviation (SD): 27,382.34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of 15 (46.9%) of the 32 studies that used serological tests reported their own validation test performance, while in 13 (40.6%), the validation performed by other studies or by the manufacturer was described. Excluding Wuhan's (China) screening programme 17 that tested 9,899,828, at least 394,090 individuals were tested in the other 36 studies that reported the number of tests. However, this number was highly variable among studies (mean: 10,946.94, median: 1990, standard deviation (SD): 27,382.34).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies demonstrated a disproportionate seroprevalence in black communities, 24,40,42–44,46,47,51 multiracial, Hispanic, Indigenous, and Asian persons, 24,34,38,39,44,46 as well as in public‐facing workers 17,24,43 and slums population 18,45 . These data show the disparities that minority communities face to access healthcare systems, arisen from a complex relationship of social, environmental, economic and structural inequities 60,61 .…”
Section: Discussionmentioning
confidence: 97%
“…Some studies demonstrated a disproportionate seroprevalence in black communities ( 24,40,42-44,46,47,51 ), multiracial, hispanic, indigenous, and asian persons ( 24,38,39,43,44,46 ), as well as in public-facing workers ( 17,24,43 ), and slums population ( 18,45 ). These data show the disparities that minority communities face to access healthcare systems, arisen from a complex relationship of social, environmental, economic, and structural inequities ( 60,61 ).…”
Section: Discussionmentioning
confidence: 99%